Fundamentals of Financial Management - James C. Van Horne; John M. Wachowicz (England Pearson Education Limited, 2008)
A practical introduction to understanding the Financial Management of companies in today's rapidly changing business world. This book is particularly well-suited to introductory courses in financial management, for a professional qualification and as a reference for practitioners.
Keywords: Economics; Business; Finance